Arm coordination, power, and swim efficiency in national and regional front crawl swimmers - Seifert, L.; Toussaint, H. M.; Alberty, M.; Schnitzler, C.; Chollet, D. (Human Movement Science, 2010)
The effects of skill level on index of arm coordination (IdC), mechanical power output (Pd), and swim efficiency were studied in front crawlers swimming at different speeds. Seven national and seven regional swimmers performed an arms-only intermittent graded speed test on the MAD-system and in a free condition. The MAD-system measured the drag (D) and Pd. Swimming speed (v), stroke rate (SR), stroke length (SL), stroke index (SI), relative entry, pull, push, and recovery phase durations, and IdC were calculated. Swim efficiency was assessed from SI, the coefficient of variation of calculated hip intra-cyclic velocity variations (IVV), and the efficiency of propulsion generation, i.e., the ratio of v2 to tangential hand speed squared (u2). Both groups increased propulsive continuity (IdC) and hand speed (u) and applied greater Pd to overcome active drag with speed increases (p < .05). This motor organization adaptation was adequate because SI, IVV, and v2/u2 were unchanged. National swimmers appeared more efficient, with greater propulsive continuity (IdC) and Pd to reach higher v than regional swimmers (p < .05). The regional swimmers exhibited a higher u and lower SI, IVV, and v2/u2 compared to national swimmers (p < .05), which revealed lower effectiveness to generate propulsion, suggesting that technique is a major determinant of swimming performance.